DIFFERENTIAL EFFECTS OF DAY AND NIGHT TEMPERATURES ON GROWTH OF WHEAT CROP - VENKATRAMANAN, V.; Singh, S.D. (Annals of Agricultural Research, 2014)
Climate change is no longer a distant threat, it is an emerging reality. Climate change is the defining challenge of our generation. High temperature. an imminent product of global climate change will affect agriculture through direct and indirect effects on crops. The daily minimum night time temperature increased at a faster rate than daily maximum temperature in the last century and differential increase in day and night temperature occurs for many parts of the world. Two popular wheat cultivars viz. PBW 343 and UP 2333 were subjected to different thermal treatments such as normal ambient temperature + 2.4°C during day and night + 2.8ºC during daytime only and + 2.1°C during night time only from seedling establishment to maturity. In general, HDNT (T1) followed by HDT (T2) and HNT (T3) affected the crop growth. So, high day and night temperature, product of climate change have significant impacts on wheat production systems.